(untitled) (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2022)
Many software development companies are currently expanding their operations globally. Competitive advantage and the financial profits it brings to an organization are the driving forces behind the globalization of software. The distributed nature of the software development process presents many challenges for the industry. Software process improvement in international software development is one of the major difficulties. Adopting software process improvement has a large positive impact on most software development organizations. In terms of research and generally accepted standards, this has gotten a lot of attention. To help software process improvement (SPI), practitioners properly plan SPI implementation methods. This study’s goal is to arm them with enough knowledge about the types of difficulties that contribute to successful SPI implementation. This study offers a thorough examination of software process improvement in the context of international software development. Through this study, we have identified seven factors (Management Commitment, Active Involvement of Staff, Relationship, Resource Allocation, Project Team training, SPI Goal Setting, SPI awareness) as critical success factors and five factors (Availability of Resources, Staff Experience, Organizational Policies, Time Pressure, Frequent Staff Turnover) as barriers for successful implementation of software process improvement in global software development. Additionally, how the critical success factors and barriers affect the productivity and implementation of software process improvement in global software development are illustrated.